Voyage to Next - Hubley, John; Hubley, Faith (Lightyear, 1993)
Voyage to Next (1974): Mother Earth and Father Time narrate this plea for world cooperation and understanding. [www.bcdb.com] / The Tender Game (1958): A stirring rendition of "Tenderly" provides the jazz improvisational backdrop for the age-old story of boy falling head over heels for girl. [www.bcdb.com] / Eggs (1971): The Goddess of Fertility and her partner Death fight over the future of humankind until a whimsical Supreme Being intercedes. [www.bcdb.com] / Urbanissimo (1967): A comic allegory in which a runaway "city" on legs matches wits with a wily farmer. A farmer has an encounter with a runaway "city" (which devours its environs). He deserts his rural home for the imagined joys of urban life. [www.bcdb.com] / Harlem Wednesday (1959): The paintings of Gregorio Prestopino convey the sights and sounds of a day in Harlem. [www.bcdb.com] / Adventures of an * (1957): A baby, represented by the "*" symbol, enjoys the visual excitement of the world. As he grows, his appreciation dwindles. Then, as his child grows, the flame rekindles. The maturing process of man, symbolized by the figure "*", is depicted, showing how an adult again sees the world through his own child. [www.bcdb.com]